Learning Methods in Shaping The Character of Students at It Hafizhan Al Irsyad Junior High School in The Perspective of Al-Qur'an And Hadis - Nugraha, Boby Rizky; Abrianto, Danny (Riwayat: Educational Journal of History and Humanities, 2025)
Character building is an important aspect in religious-based education, especially in Islam. Good character reflects the understanding and application of the values of the Qur'an and Hadith in everyday life. The Prophet Muhammad SAW emphasized the importance of knowledge in building Islamic character. However, the development of technology and social media in the era of globalization has created a major challenge for the formation of student character. This study aims to determine the learning method in forming the character of students at SMP IT Hafizhan Al Irsyad from the perspective of the Qur'an and Hadith. This study uses a qualitative approach method, this study explores data through interviews, observations, and documentation. The results of this study are: (1) Several methods that will be taught to students, such as methods, discussion methods, problem-solving methods, habituation methods, exemplary methods. (2) Learning implementation plans (RPP) that have been prepared by Islamic Religious Education teachers and media that will be used during the teaching and learning process such as: computers, projectors and textbooks.